Odpowiedzi

  • Użytkownik Zadane
2010-01-25T18:11:45+01:00
7x-4=x+2
7x-x=2+4
6x=6/:6
x=1


-5x+4=x-8
-5x-x=-8-4
-6x=-12/:(-6)
x=2



-2x-7=2x-7
(zadanie niekompletne)

-7x+5=11x+41
-7x-11x=41-5
-18x=36/:(-18)
x=-2



36x-14=14x-36
36x-14x=-36+14
22x=-22/:22
x=-1
1 1 1
2010-01-25T18:18:49+01:00
7x-4=x+2
7x-x=2+4
6x=6 I:6
x=1

-5x+4=x-8
-5x-x=-8-(-4)
-6x=-4 I*(-1)
6x=4 I:6
x=2/3

-2x-7=2x-7
-2x-(-2x)=7-7
-4x=0 I*(-1)
4x=0 I:4
x=0

-7x+5=11x+41
-7x-(-11x)=41-5
4x=36 I:4
x=9

36x-14=14x-36
36x-14x=-36+14
22x=-22 I:22
x=-1